Solution of the First-Passage Problem by Advanced Monte Carlo Simulation Technique - Labou, M. (Проблемы прочности, 2003)
A selective Monte Carlo simulation procedure for the evaluation of the reliability of nonlinear structures subjected to dynamic loading is presented. The proposed “Russian Roulette and Splitting” procedure allows generation of important low-probability samples in nonlinear dynamics. This procedure is quite efficient in comparison to the straightforward Monte Carlo simulation method and allows evaluation of the nonlinear stochastic response in a very low probability domain.